Securing the Sacred : Religion, National Security, and the Western State - Bosco, Robert M. (Book collections on Project MUSE., 2014)
"Since the terrorist attacks of September 11, 2001, Western nations have increasingly recognized religion as a consideration in domestic and foreign policy. In this empirical comparison of the securitization of Islam in Britain, France, and the United States, Robert M. Bosco argues that religion is a category of phenomena defined by the discourses and politics of both religious and state elites. Despite significant theoretical distinctions between securitization on the domestic and the international levels, he finds that the outcome of addressing religion within the context of security hinges upon partnerships. Whereas states may harness the power of international allies, they cannot often find analogous domestic allies; therefore, states that attempt to securitize religion at home are more vulnerable to counterattack and more likely to abandon their efforts. This book makes a significant contribution to the fields of political theory, international relations, Islamic studies, and security/military studies."--Publisher's summary